Narrative inquiry into the lives of physical education teachers: in pursuit of physical literacy - Leiss, Jodie (Kansas State University, 2016)
This study is a narrative inquiry into the lives of physical education teachers in order to gain insight into their identities as physical education teachers and their understanding of what it means to be physically literate as well as investigate into the thoughts of physical education teachers about the concept of comprehensives school physical activity programs. According to Whitehead (2010), physical literacy is a disposition to capitalize on the human embodied capability, wherein an individual has the motivation, confidence, physical competence, knowledge and understanding to value and take responsibility for maintaining purposeful physical pursuits/activity throughout a lifetime. Development of the debate regarding physical literacy was stimulated by the study of existentialist and phenomenological philosophers, such as Sartre and Merleau-Ponty, who articulate a particular stance towards the nature of our mind and body connection. Merleau-Ponty’s (1945/2010) philosophy facilitated the gain of knowledge regarding 1) how stories of physical education teachers help promote physical literacy in schools; 2) how physical education teachers perceive the mind/body connection; and 3) how physical education teachers understand what it means to be physically literate. The contributions to the thought and practice of physical education as a result of this study will highlight 1.) physical literacy is embodied in adapted physical education; 2.) the role of physical education teachers is not just teaching and moving the body, but to help students learn better; 3.) A stressed mind affects the body, and having a healthy body helps students learn better; 4.) A new role of physical education teachers is to bridge the gap between physical education and the classroom by providing ideas to classroom teachers regarding brain breaks. 5.) Teacher education programs need to highlight reflective practices that help future physical educators draw upon knowledge from their own life experiences to enrich their teaching; 6.) Physical education teachers should collaborate with public health officials to implement comprehensive school physical activity programs.
Keywords: Narrative Inquiry; Teacher IdentityPhysical Literacy